Ethnic Background and the Value of Self-Employment Experience: Evidence from a Randomized Field Experiment - Lina Aldén; Spencer Bastani; Mats Hammarstedt (Research Institute of Industrial Economics (IFN), 2020)
In this paper, we use a randomized field experiment in Sweden to investigate how self-employment experience is valued in the labor market. We find that self-employment experience negatively impacts the probability of receiving a positive response from employers. For male applicants, this holds regardless of their ethnic background, and independently of whether we consider applicants with experience solely from self-employment, or applicants with a mix of experience from wage-employment and self-employment. For female applicants, the results are less clear-cut. Our findings provide input into the discussion about the impact of self-employment on the chances for natives and immigrants to obtain wage-employment.
Keywords: J15; J24; J71; L26; 330; Self-employment; Wage-employment; Randomized experiment; Discrimination; Labor market outcomes